Inside Cambodian insurgency a sociological perspective on civil wars and conflict - Bultmann, Daniel (Military strategy and operational art, 2015)
There are many different types of power practice directed towards making soldiers obedient and disciplined inside the field of insurgency. This book puts forth that the type of power being utilised depends on the habitus of the respective commander and, as a result, becomes socially differentiated.